Revelles-Benavente, Beatriz y González Ramos, Ana Mª (Eds.). Teaching Gender: Feminist Pedagogy and Responsibility in Times of Political Crisis - Sola García, Marina (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2017)
Este artículo reseña: Revelles-Benavente, Beatriz y González Ramos, Ana Mª (Eds.). Teaching Gender: Feminist Pedagogy and Responsibility in Times of Political Crisis. London: Routledge, 2017, 204 p. [978-1-13-870123-6]